2008
DOI: 10.1007/s00381-008-0686-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep sylvian meningioma: a case report and review of literature

Abstract: At 4-year follow-up, he was asymptomatic, and there was no tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Deep sylvian meningiomas are a very rare entity. 2 To our knowledge, including the present case, only 27 cases are reported in the international literature (►Table 1). According to some authors, these meningiomas probably arise from arachnoid cap cells that are found in the Virchow-Robin spaces along the cerebral vasculature.…”
Section: Discussionmentioning
confidence: 72%
“…Deep sylvian meningiomas are a very rare entity. 2 To our knowledge, including the present case, only 27 cases are reported in the international literature (►Table 1). According to some authors, these meningiomas probably arise from arachnoid cap cells that are found in the Virchow-Robin spaces along the cerebral vasculature.…”
Section: Discussionmentioning
confidence: 72%
“…Microsurgical resection of these tumors has been reasonably successful in reducing seizures, especially when complete resection is achieved. 5,11,17,23 Our patient who underwent total resection of the meningioma has remained seizure-free for 10 years, but the other patient with subtotal resection has continued to experience seizures associated with tumor recurrence and progression from WHO grade I to grade II histology. Although complete resection was difficult in this second patient because of the intraparenchymal location, the main reason it was deemed high risk was dense adherence of the tumor to the distal MCA branches in the dominant hemisphere.…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3][4] Sylvian fissure meningiomas are extremely rare, with only 24 previously reported cases in the world literature, almost all occurring in children. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] We report two additional cases of children with deep sylvian fissure meningiomas without dural attachment and an additional case of meningioangiomatosis (MA) in the perisylvian region. The literature is also reviewed regarding similarities and differences with the other small number of cases previously described.…”
mentioning
confidence: 99%
“…However, its radiological appearance is frequently non-specific and a definitive preoperative diagnosis is difficult. Out of the 25 cases of deep sylvian meningiomas that have been reported in the literature2,8,9,12), benign histology is the most common diagnosis (97%)4).…”
Section: Discussionmentioning
confidence: 99%